2017
DOI: 10.1038/srep40880
|View full text |Cite
|
Sign up to set email alerts
|

The association of bacterial C9-based TTX-like compounds with Prorocentrum minimum opens new uncertainties about shellfish seafood safety

Abstract: In 2012, Tetrodotoxin (TTX) was identified in mussels and linked to the presence of Prorocentrum minimum (P. minimum) in Greece. The connexion between TTX and P. minimum was further studied in this paper. First, the presence of TTX-producer bacteria, Vibrio and Pseudomonas spp, was confirmed in Greek mussels. In addition these samples showed high activity as inhibitors of sodium currents (INa). P. minimum was before associated with neurotoxic symptoms, however, the nature and structure of toxins produced by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 41 publications
1
44
1
Order By: Relevance
“…Unlike many other marine toxins, which are of microalgal origin, TTX production is thought to be produced by bacteria of the genera Pseudomonas, Shewanella, Alteromonas or Vibrio [7], in symbiosis with certain animals [8]. Recently, the marine dinoflagellate Prorocentrum minimum has been described to produce TTXs in cultures, with possible implication of endosymbiotic bacteria [9].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike many other marine toxins, which are of microalgal origin, TTX production is thought to be produced by bacteria of the genera Pseudomonas, Shewanella, Alteromonas or Vibrio [7], in symbiosis with certain animals [8]. Recently, the marine dinoflagellate Prorocentrum minimum has been described to produce TTXs in cultures, with possible implication of endosymbiotic bacteria [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, a similar trend between TTX in shellfish and P. minimum was not observed in samples from the UK [4]. More recently, TTX-like compounds were identified in cultures of P. minimum [11].…”
Section: Introductionmentioning
confidence: 75%
“…The presence of Vibrio parahaemolyticus, Vibrio alginolyticus and Pseudomonas spp. were confirmed in TTX contaminated mussels from the Greek and UK coasts [3,11]. In addition, the hypothesis of phytoplankton species, namely Prorocentrum minimum, as a source of TTX to bivalves, has been raised by [12] after correlating TTX in shellfish and algae occurrence in the Greek coast.…”
Section: Introductionmentioning
confidence: 90%
“…Rodríguez et al [62] identified several Vibrio and Pseudomonas bacteria, which had previously been reported in TTX production, in contaminated shellfish samples collected in Greece. Most of the TTX-producing strains found in the puffer fish were isolated from the intestine and ovary (63%); others were isolated from the liver (13%), skin and slime on the skin surface (17%), and the total extract of the internal organs (7%).…”
Section: Ecology Of Marine Ttx-producing Bacteriamentioning
confidence: 99%